Inviting all the world's crops to the table: supporting traditional crops to supply future needs - Hart, H. (2007)
”Inviting all the world's crops to the table” was prepared by the Global Facilitation Unit for Underutilized Species (GFU), in cooperation with Bioversity International. This publication is another effort of GFU to raise awareness of the importance of underutilized plant species for improving peoples' livelihoods. It underscores the findings of the Chennai Platform for Action, which grew out of an international consultation held in Chennai, India, in April 2005. This meeting, organized by GFU, Bioversity International and the M.S. Swaminathan Research Foundation was attended by policymakers and experts from 25 countries around the world and formulated approaches to maximize the contribution of agricultural biodiversity to reducing hunger and poverty. It has only been in the last decade that policymakers and the public havestarted to awaken to the fact that quality of life is dependent not only on quantity of food but also on high quality food from diverse sources. It took the drastic simplification of global agriculture with its shrinking basket of agricultural choices and looming population growth figures to get their attention. With this awareness has come a recognition that a huge proportion of the world's lesser known traditional food crops have been left out of the agricultural advances of recent decades, neglected by scientists, who concentrate on only a few of the major staples. Yet these traditional crops have great potential for providing the world's population with a choice of nutritious foods and other needed products.This booklet has been prepared to present a positive look at what supporting the development of neglected and underutilized crops and refilling the agricultural basket can mean in terms of health, income, culture and the global environment. By highlighting just a few examples of what these crops have to offer, the story becomes quite clear: when crops are ignored by research and not adopted by commercial farmers, the entire world loses.